Improving Learning Outcomes by Using Quizizz Educational Game Assisted Learning Video Media - Anik Hariyastuti (Universitas Sebelas Maret, 2020)
This study aims to determine the increase in learning outcomes in online learning through learning video media assisted by quiziz educational games. This research is a classroom action research with 29 students of class V SDN Adiwerna 01 as the research subjects. This research was conducted in 2 cycles, each cycle of 2 meetings. Each meeting consists of 4 stages, namely planning, implementing, observing and reflecting. The implementation of the research stages is slightly different from classroom learning because learning is carried out separately or students are in their respective homes. Based on the results of the research, in the first cycle, the average student learning outcomes were 72.07 with 72% student completeness success, still below the 85% success indicator. Whereas in cycle II the average student learning outcomes were 82, 07 and the completeness success increased to 93% in this case it was more than the 85% achievement indicator. So from cycle I and cycle II there was an increase in student learning outcomes. So, in this study it can be concluded that using video learning media assisted by quiziz educational games can improve student learning outcomes in online learning science subjects human digestive organs material.